Comparison of two oral probiotic preparations in a randomized crossover trial highlights a potentially beneficial effect of Lactobacillus paracasei NCC2461 in patients with allergic rhinitis. Issue 1 (6th January 2014) - Perrin, Yannick; Nutten, Sophie; Audran, Régine; Berger, Bernard; Bibiloni, Rodrigo; Wassenberg, Jacqueline; Barbier, Nathalie; Aubert, Vincent; Moulin, Julie; Singh, Anurag; Magliola, Corinne; Mercenier, Annick; et al.
Abstract: Background: There is promising but conflicting evidence to recommend the addition of probiotics to foods for prevention and treatment of allergy. Based on previous studies with fermented milk containing Lactobacillus paracasei NCC2461, we aimed to compare the effect of a powder form of the latter probiotic with the effect of a blend of Lactobacillus acidophilus ATCC SD5221 and Bifidobacterium lactis ATCC SD5219 in patients with allergic rhinitis. Methods: A double‐blind, randomized, cross‐over study, involving 31 adults with allergic rhinitis to grass pollen, was performed outside the grass pollen season (registration number: NCT01233154). Subjects received each product for 4‐weeks in two phases separated by a wash‐out period of 6 to 8 weeks. A nasal provocation test was performed before and after each 4‐week product intake period, and outcome parameters (objective and subjective clinical symptoms; immune parameters) were measured during and/or 24 hours after the test. Results: Out of the 31 subject enrolled, 28 completed the study. While no effect was observed on nasal congestion (primary outcome), treatment with NCC2461 significantly decreased nasal pruritus (determined by VAS), and leukocytes in nasal fluid samples, enhanced IL‐5, IL‐13 and IL‐10 production by peripheral blood mononuclear cells in an allergen specific manner and tended to decrease IL‐5 secretion in nasal fluid, in contrast to treatment with the blend of L. acidophilus and B. lactis . Conclusions: Despite short‐term consumption, NCC2461 was able to reduce subjective nasal pruritus while not affecting nasal congestion in adults suffering from grass pollen allergic rhinitis. The associated decrease in nasal fluid leukocytes and IL‐5 secretion, and the enhanced IL‐10 secretion in an allergen specific manner may partly explain the decrease in nasal pruritus. However, somewhat unexpected systemic immune changes were also noted. These data support the study of NCC2461 consumption in a seasonal clinical trial to further demonstrate its potentially beneficial effect.